2018
DOI: 10.18689/mjcrs-1000107
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Topical and Systemic Effects of Omega-3 on Oral mucosal wound healing in albino rats: A Histopathological and Biochemical study

Abstract: The use of herbal medicine is increasingly becoming more accepted in treatment of many inflammatory conditions. Omega-3 is recently introduced as an effective therapeutic agent and a powerful anti-inflammatory agent, which promotes whole-body wound healing including ulcers as it has an important role in modulation of proinflammatory cytokine production. This study was conductedto evaluate and compare the effect of topicalapplication and systemic administration of omega-3 on the healing of oral mucosal wounds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…Despite the difference in the etiopathogenesis between RAS and RIOM, the study highlights the influence of omega-3 intake on mucosal recovery [ 72 ].This can be related to the ability of EPA and DHA, on a cellular level, to maintain epithelial integrity and cell barrier function by preventing disruption in tight junction structure and decreasing cell necrosis [ 73 ]. In addition, our results of topical protective action of Omega-3 nanoemulgel are comparable with Basha et al [ 28 ] who demonstrated a significant enhancement in oral mucosal wound healing in rats treated topically by omega-3 compared to its systemic administration.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Despite the difference in the etiopathogenesis between RAS and RIOM, the study highlights the influence of omega-3 intake on mucosal recovery [ 72 ].This can be related to the ability of EPA and DHA, on a cellular level, to maintain epithelial integrity and cell barrier function by preventing disruption in tight junction structure and decreasing cell necrosis [ 73 ]. In addition, our results of topical protective action of Omega-3 nanoemulgel are comparable with Basha et al [ 28 ] who demonstrated a significant enhancement in oral mucosal wound healing in rats treated topically by omega-3 compared to its systemic administration.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, multiple studies have highlighted the effect of Omega-3 supplements’ consumption in maintaining body weight/composition and improving (QoL) of cancer patients [ 25 , 26 ]. This is possibly attributed to their anti-inflammatory and anti-oxidant effects, and also their role in maintaining epithelial integrity and promoting whole-body wound healing [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may be connected to EPA and DHA's capacity to preserve cell barrier function and epithelial integrity at the cellular level by avoiding tight junction structure disruption and reducing cell necrosis (36). Moreover, the topical protective role of Omega-3 emulgel demonstrated in our results are comparable to the findings of Basha et al who showed a significant enhancement in rats oral mucosal healing after being treated by topical Omega-3, compared to those treated by systemic administration (13). Similarly, the overall topical preventive effect of Omega-3 on OM is also aligned with Ferreira, P. et al who stated that vitamin E mouthwash lowered the incidence of symptomatic RIOM in oral and oropharyngeal cancer patients (37).…”
Section: Discussionsupporting
confidence: 86%
“…A growing body of research, including both human and animal studies, has demonstrated the therapeutic benefits of Omega-3 PUFAs, particularly EPA and DHA, in a number of human diseases, including diabetes, cancer, cardiovascular problems, and autoimmune disorders (9,11). This may be related to their anti-inflammatory and antioxidant properties, and also their support for epithelial integrity and wound healing ability (12,13). It was discovered that Omega-3 PUFAs lower levels of pro-inflammatory cytokines that include (TNFα), (IL-6) and (IL-1β) in addition to inhibiting arachidonic acid metabolites production which can limit tissue damage and actively suppress inflammation (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation